2012
DOI: 10.1371/journal.pone.0031974
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Periostin as a Critical Marker of Progression/Reversal of Hypertensive Nephropathy

Abstract: Progression of chronic kidney disease (CKD) is a major health issue due to persistent accumulation of extracellular matrix in the injured kidney. However, our current understanding of fibrosis is limited, therapeutic options are lacking, and progressive degradation of renal function prevails in CKD patients. Uncovering novel therapeutic targets is therefore necessary.We have previously demonstrated reversal of renal fibrosis with losartan in experimental hypertensive nephropathy. Reversal was achieved provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 30 publications
4
77
0
Order By: Relevance
“…Various human and experimental renal diseases affect the glomerular podocytes that form the final filtration barrier, leading to proteinuria. [31][32][33] Molecular changes of the slit diaphragm following any pathologic alterations in the podocytes will eventually result in restructuring of the arrangement in the foot process with the fusion of filtration slits and apical shift of the slit diaphragm. [34][35][36] Nestin, an intermediate filament protein primarily identified in neural stem cells, is transiently expressed in the glomerular podocytes of the adult kidney that are linked with the maintenance of the foot process structure.…”
Section: Introductionmentioning
confidence: 99%
“…Various human and experimental renal diseases affect the glomerular podocytes that form the final filtration barrier, leading to proteinuria. [31][32][33] Molecular changes of the slit diaphragm following any pathologic alterations in the podocytes will eventually result in restructuring of the arrangement in the foot process with the fusion of filtration slits and apical shift of the slit diaphragm. [34][35][36] Nestin, an intermediate filament protein primarily identified in neural stem cells, is transiently expressed in the glomerular podocytes of the adult kidney that are linked with the maintenance of the foot process structure.…”
Section: Introductionmentioning
confidence: 99%
“…14 We reported that periostin is highly upregulated during disease progression and inversely downregulated during regression in a model of hypertensive renal disease. 15 Although the above results indicate that periostin can be a new biomarker of renal disease progression, whether periostin participates in the development of CKD has not been examined. This hypothesis was investigated in the present study using two complementary approaches: mice lacking periostin (Postn null mice) and in vivo administration of antisense (AS) oligonucleotides (ODNs) in hypertensive rats.…”
mentioning
confidence: 96%
“…13 We previously reported that periostin expression is highly correlated with disease progression in a model of hypertensive nephropathy, and we subsequently showed that mice lacking periostin are protected against the structural alterations induced by unilateral ureteral obstruction. 14,15 Despite these findings, the mechanisms of induction and function of periostin in renal disease are largely unknown. In this study we investigated these mechanisms in an established chronic renal disease model induced by nephrotoxic serum (NTS) administration.…”
mentioning
confidence: 99%